The Datums Transformation for GPS Navigation Measurements Correction (Baghdad Science Journal, 2008)
The GPS navigation measurements become more widely used in many civilian and scientific application. All GPS navigation data holds many errors, the main error sources arise from the geodetic Datum variation when user apply the GPS measurements with the map. Geodetic datums define the size and shape of the earth and the origin and orientation of the coordinate systems used to map the earth surface. In this paper, the Datum transformation was evaluated in two mathematical methods to overcome the errors due to the difference between the WGS-84 and our country Datum Clarck-1880. The results was evaluated and investigated using Carmin GPS device for GCPs comparison, topographic map for Hilla city, mid Iraq 1:100000 scale, and two georefrencing ETM+ & TM satellite images. The spatial transformation error was less than 10 meter for UTM projection & less than 1 sec for (?, ?) projection, which can considered as suitable results in transformation calculation All results were overcome using two written program for each method with the help of Matlab facility.GPS: Global Positioning System, GCPs: Ground Control Points